Verkehrte Leidenschaft Gleichgeschlechtliche Unzucht im Kontext von Strafrecht und Medizin, Aus- und Verhandlungsprozesse vor dem Landesgericht Linz 1918-1938 - Greif, Elisabeth (Jan Sramek Verlag, 2019)
The book scrutinizes the legal-historical development of the crime "unnatural fornication". The analysis focuses on contemporary law and sexual science sources as well as files from criminal proceedings for same-sex fornication. lt shows how different negotiation processes influenced the ideas of the "immoral", thesexual and the gender.